VR환경에서의 3차원 촉각 정보 피드백을 위한 가변형 천 구동기 - Jeon Jun-Sang; Song, Kahye (2023년도 IT융합부문 춘계학술대회 논문집, 2023)
Tactile feedback actuator research has been actively conducted due to enable realistic tactile feedback in virtual reality. (1). Traditional rigid-based actuators enable intuitive feedback to the hand, but increasing the number of degrees of freedom for different tactile realizations (e.g. skin deformation and shear forces) requires more actuators, making the system bulky (2). To overcome this problem, research has focused on developing compact, lightweight, and flexible actuators (3). In this paper, a variable shape actuator was presented that could provide tactile feedback of a shape. The actuator consisted of a square plane actuator and a triangular prism actuator. The shape of the variable shape actuator could change the angle of the square plane actuator through a combination of contraction and expansion created by triangular prism actuators. As the square plane actuator was expanded, it gave tactile feedback to the user's hand. The virtual object shapes used in this study were a rectangle and a circle with distinct angles between the corners. In the case of circles, the shape was estimated by dividing the distance between the index finger and thumb into smaller and larger cases than the diameter of the circle. Data on the paths of the tactile feedback actuator’s surface touched the hand and the theoretical shape estimated from the actuator length were compared. The results showed that the smaller circle case was the smallest error rate of 2.16% between estimation and experiment. Conversely, the same shape but with the larger circle case had the largest error rate of 11.29%. This is due to the inclusion of surface paths that do not provide tactile feedback, i.e., areas beyond the reach of the hand. Developing these actuators can be used in many ways for tactile feedback actuators in soft robotics.